Double-edged sword: The effect of exergaming on other forms of exercise; a randomized controlled trial using the self-categorization theory. (September 2016) - Nguyen, Huynh Van; Huang, Han-Chung; Wong, May-Kuen; Lu, Ju; Huang, Wei-Fan; Teng, Ching-I
Abstract: Background: No study has yet adopted the perspective of the self-categorization theory to examine the impact of playing exergames on players' attitudes and intentions towards other forms of exercise. Purpose: To examine the impact of playing exergames on players' attitudes and intentions to engage in other exercise and how such an impact depends on previous exercise frequency. Methods: This randomized controlled trial recruited 117 college students who were randomly assigned to either an intervention group (n = 55) or a control group (n = 62). Participants in the first group played an exergame for 30 min, three times per week for 12 weeks. This study calculated the changes in the participants' attitudes and intentions before and after the program, and compared the differences between the two groups. Results: Exergaming improved the players' attitudes toward other forms of exercise. Such improvement was significant for frequent exercisers, but not for infrequent exercisers. Surprisingly, playing exergames strengthened the intentions to engage in other forms of exercise for frequent exercisers, but weakened such intentions for infrequent exercisers. Conclusions: Exergaming encourages frequent exercisers to engage in other forms of exercise, but does the opposite among infrequent exercisers. Originality: This study is the first identifying the contingent effect of exergaming on users' attitudes and intentions toward other forms of exercise. Highlights: This study examines how exergaming impacts attitudes and intention to do other exercise. Playing exergames improves attitude toward other forms of exercise. Users' previous exercise frequency moderates such improvement.